Melanoma in Peru: 1000 patients and 10 years of experience - Gonzalo Ziegler-Rodriguez; Gabriel De la Cruz-Ku; Anshumi Desai; Luis Piedra Delgado; Silvana Maldonado; Jiddu Antonio Guart; Camila Franco; Sheyla Diaz-Mora; Sheila Vilchez Santillan; Jorge Dunstan Yataco; Juan Haro-Varas; Jose Galarreta Zegarra; et al. (PLoS ONE, 2025)
Background Epidemiological studies identify characteristics of melanoma based on race and ethnic groups. Previous reports have revealed that the Hispanic/Latino population with melanoma has different characteristics compared to other races. We aimed to describe the sociodemographic, clinicopathological features, and long-term outcomes such as event-free survival (EFS) and overall survival (OS) Peruvian population with melanoma. Methods We conducted a retrospective cohort study of new cases diagnosed and treated at a single tertiary institution from 2010 to 2019. Survival analysis included patients with stages I-IV. Multivariable Cox Regression analysis was used to assess prognostic factors. Results A total of 1136 patients were included, the median age at diagnosis was 63 years old (6−97 years), the majority were males (51.5%), resided in a non-metropolitan area (77.7%), had a primary lesion in lower extremities (75.5%), ulceration (52.4%), and acral lentiginous was the most common histological subtype (38.1%). The mean Breslow was 8.88, and 6.62 number of mitoses per mm. Stage T3-4 was present in 70.4%, while Stage III was the most frequent AJCC Stage (36.5%). Regarding adjuvant therapy, 13.4% received chemotherapy, 3.6% radiotherapy, and 13.6% interferon. No patients received immunotherapy. At 5-year follow-up, the EFS was 20%, while the OS was 36%. Prognostic factors of worse EFS were greater age (HR = 1.020), male sex (HR = 1.369), greater mitotic rates (HR = 1.012), ulceration (HR = 1.564), positive lymph nodes (HR = 2.58), while primary lesion in upper extremities (HR = 0.518) was associated to better EFS. Prognostic factors of worse OS were greater age (HR = 1.024), greater mitotic rate (HR = 1.013), ulceration (HR = 1.72), and positive lymph nodes (HR = 3.231). Conclusions The sociodemographic features of Peruvian patients with melanoma are different from other populations. There were higher stages without access to immunotherapy, therefore EFS and OS rates were worse than international reports, while prognostic factors were similar. Urgent healthcare policy changes are needed as is access to immunotherapy.